A Review of GM-CSF Therapy in Sepsis. Issue 50 (December 2015) - Mathias, Brittany; Szpila, Benjamin E.; Moore, Frederick A.; Efron, Philip A.; Moldawer, Lyle L.
Abstract : Abstract: Determine what clinical role, if any, GM-CSF may have in the clinical treatment of sepsis in the adult patient. Advancements in the management of sepsis have led to significant decreases in early mortality; however, sepsis remains a significant source of long-term mortality and disability which places strain on healthcare resources with a substantial growing economic impact. Historically, early multiple organ failure (MOF) and death in patients with severe sepsis was thought to result from an exaggerated proinflammatory response called the systemic inflammatory response syndrome (SIRS). Numerous prospective randomized controlled trials (PRCTs) tested therapies aimed at decreasing the organ injury associated with an exaggerated inflammatory response. With few exceptions, the results from these PRCTs have been disappointing, and currently no specific therapeutic agent is approved to counteract the early SIRS response in patients with severe sepsis. It has long been recognized that there is a delayed immunosuppressive state that contributes to long-term morbidity. However, recent findings now support a concurrent proinflammatory and anti-inflammatory response present throughout sepsis. Multiple immunomodulating agents have been studied to combat the immunosuppressive phase of sepsis with the goal of decreasing secondary infection, reducing organ dysfunction, decreasing ICU stays, and improving survival. Granulocyte-macrophage colony stimulating factor (GM-CSF), a myelopoietic growth factor currently used in patients with neutropenia secondary to chemotherapy-induced myelosuppression, has been studied as a potential immune-activating agent. The applicability of GM-CSF as a standard therapy for generalized sepsis is still largely understudied; however, small-scale studies available have demonstrated some improved recovery from infection, decreased hospital length of stay, decreased days requiring mechanical ventilation, and decreased medical costs.